Performance of the IS6110-TaqMan® assay in the diagnosis of extrapulmonary tuberculosis from different biological samples - Fabiana Cristina Fulco Santos; Laís Ariane de Siqueira Lira; Rosana de Albuquerque Montenegro; Juliana Figueirêdo da Costa Lima; Andrea Santos Lima; Haiana Charifker Schindler; Lílian Maria Lapa Montenegro (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: This study evaluated the performance of the IS6110-TaqMan® assay in different types of biological samples and tissues for laboratory diagnosis of extrapulmonary tuberculosis. METHODS: 143 biological samples and tissues from patients with suspected extrapulmonary tuberculosis from the health services of Recife/Pernambuco/Brazil were evaluated with the IS6110-TaqMan® assay. RESULTS: The sensitivities of the IS6110-TaqMan® assay calculated for blood, urine, both blood and urine samples, tissue biopsies, extrapulmonary body fluid samples, and all samples from patients calculated together were 55.9%, 33.3%, 68.8%, 43.8%, 29.6%, and 73.7%, respectively, and the specificities were 80%, 100%, 78.6%, 100%, 100%, and 84.2%, respectively. CONCLUSIONS The accuracy of qPCR was high in various clinical sample types. The analysis of more than one type of clinical sample collected from the same patient with extrapulmonary tuberculosis enhances the diagnostic power of the IS6110-TaqMan® assay when compared with the use of only one clinical sample.